Outcomes of arthroscopic debridement and microfracture for osteochondral lesions of the talus - Bozkurt, Celal; Sarikaya, Baran; Sipahioglu, Serkan; Akif Altay, Mehmet; Erdem Isikan, Ugur (Annals of Medical Research, 2021)
None
Keywords: Talus; Osteochondral lesion; Microfracture.